2022
DOI: 10.1002/path.5996
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated cancer cells detected by immunocytology in lymph nodes of NSCLC patients are highly prognostic and undergo parallel molecular evolution

Abstract: In melanoma, immunocytology (IC) after sentinel lymph node disaggregation not only enables better quantification of disseminated cancer cells (DCCs) than routine histopathology (HP) but also provides a unique opportunity to detect, isolate, and analyse these earliest harbingers of metachronous metastasis. Here, we explored lymph node IC in non‐small cell lung cancer (NSCLC). For 122 NSCLC patients, 220 lymph nodes (LNs) were split in half and prepared for IC and HP. When both methods were compared, IC identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Then, we tested whether EpCAM‐positive cells from LNs confer prognostic information. Here, we found detection of EpCAM‐positive DCCs to be the most informative variable for outcome prediction in multivariable analysis 17 …”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Then, we tested whether EpCAM‐positive cells from LNs confer prognostic information. Here, we found detection of EpCAM‐positive DCCs to be the most informative variable for outcome prediction in multivariable analysis 17 …”
Section: Introductionmentioning
confidence: 68%
“…Apparently, a high number of DCCs in LNs reflects a proliferative phenotype and genotype that also enables sphere formation. In addition, specific genomic aberrations are acquired during proliferation within the LNs, 17 which may drive sphere formation. This is consistent with observations in melanoma, where we previously found that xenograft formation and acquisition of specific alterations within the LN are intimately linked 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that (i) most of these early disseminated cancer cells (DCC) are not (yet) able to form a metastatic colony as they are lacking important genetic changes and (ii) that such changes are acquired during cell divisions within the metastatic site 2 . We therefore concluded that melanomas (and other cancers such as non-small-cell-lung cancer as well 3 ) undergo molecular evolution at distant sites in parallel to the primary tumour 4 . Yet, the metastasis founder cells and the molecular features enabling and driving this evolution are currently unknown.…”
Section: Introductionmentioning
confidence: 90%